Corporate Social Responsibility Shouldn't Do Infrastructure? Spending and Overcoming Poverty with Graduation Model Theory - Karjoko, Lego; I Gusti , Ayu Ketut Rachmi Handayani; Anom Husodo, Jadmiko; Fandra Mahira, Dararida (Magister of Law, Faculty of Law, University of Mataram, 2025)
Until now there is still a lot of poverty around plantation companies such as what happened in East Kalimantan which amounted to 80,000 and in West Java almost half of the heads of families live in poverty around PT Perkebunan Nusantara VIII which is a state-owned plantation. This Study examines efforts to overcome poverty around plantation companies through corporate social responsibility using graduation model theory based on community participation. Using a socio-legal framework, empirical legal research is the study methodology used. In an attempt to combat poverty, the plantation firms' perspectives on CSR are included in the kind of primary data. Secondary data from research on CSR and Graduation Model are then added to the main data. Methods of data collecting included literature reviews and interviews. Qualitative analytic approaches were employed in the study. A definitive description of CSR, which makes it hard for many businesses to know what it really means, according to the findings. This leads to less than ideal corporate social responsibility implementation. The community believes that they are not benefiting from the presence of plantation corporations because of this. In order to combat poverty in the area of plantation firms, it is necessary to have a clear grasp of what corporate social responsibility is and to use Graduation Model Theory to empower the community. With this research, it is hoped that it can be a solution for plantation companies to carry out CSR that is more effective for the community and can erase the bad view in the eyes of the community regarding plantation companies.